A skeletal n-butane mechanism with integrated simplification method. Issue 4 (August 2020) - Li, Fan; Yang, Haolin; Jiang, Liqiao; Huo, Jiepeng; Wang, Xiaohan; Zhao, Daiqing
Abstract: A new skeletal mechanism of n-butane is developed for describing its ignition and combustion characteristics applicable over a wide range of conditions: initial temperature 690–1430 K, pressure 1–30 atm, and equivalence ratio 0.5–2.0. Starting with a detailed chemical reaction kinetic model of 230 species and 1328 reactions (Healy et al., Combust. Flame, 2010), the directed relation graph method is applied as the first step to derive a semi-detailed mechanism with 134 species. Then, the reaction path analysis in conjunction with temperature sensitivity analysis is used to remove the redundant species and reaction paths simultaneously under the condition of low-temperature and moderate-to-high temperatures, respectively. Finally, a skeletal n-butane mechanism consisting of 86 species and 373 reactions can be obtained. Mechanism validation indicates that the new developed skeletal mechanism is in good agreement with the detailed mechanism in predicting the global ignition and combustion characteristics. The new skeletal mechanism is further validated using extensive available literature data including rapid pressure machine ignition delay time, shock-tube ignition delay time, laminar flame speed, and jet-stirred reaction oxidation, covering a large range of temperatures, pressures, and equivalence ratios. The comparison results demonstrate that a satisfactory agreement between predictions and experimental measurements is achieved. Highlights: A skeletal mechanism with 86 species and 373 reactions for n -butane oxidation was proposed. The DRG, reaction pathway analysis, and sensitivity analysis are used in combination. The skeletal model exhibits good agreement with the detailed mechanism in predicting ignition and combustion characteristics. Applicability of the current model was validated against extensive experimental data.